THE EFFECT OF USING ADVENTURE GAME AND PICTURE ON INTROVERTED STUDENTS’ SPEAKING SKILL - Rona Elfiza (Proceeding of International Conference on Art, Language, and Culture, 2017)
This article explains the result of research that aim to test whether introverted students’ speaking skill who were taught by using adventure game better than introverted student’s speaking skill who were taught by using pictures toward introverted students’ speaking skill in descriptive text of SMPN 1 Talamau. This research was a quasi experimental research. The population of this research was the VIII grade students of SMPN 1 Talamau .There were five parallel classes that totalized 125 students. The sample of this research was class VIII4 and VIII5.  The sample was selected by cluster random sampling. The instruments were questionnaire of students’ personality and speaking test. The data were analyzed by t-test formula. The result of this research were introverted students’ speaking skill who were taught by using adventure game was better than introverted students’ speaking skill who were taught by using picture. It can be concluded that adventure game gave significant effect toward introverted students’ speaking skill at SMPN 1 Talamau